2016
DOI: 10.1038/ncomms13107
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary trajectories of snake genes and genomes revealed by comparative analyses of five-pacer viper

Abstract: Snakes have numerous features distinctive from other tetrapods and a rich history of genome evolution that is still obscure. Here, we report the high-quality genome of the five-pacer viper, Deinagkistrodon acutus, and comparative analyses with other representative snake and lizard genomes. We map the evolutionary trajectories of transposable elements (TEs), developmental genes and sex chromosomes onto the snake phylogeny. TEs exhibit dynamic lineage-specific expansion, and many viper TEs show brain-specific ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
102
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(110 citation statements)
references
References 79 publications
6
102
0
2
Order By: Relevance
“…Analysis of GC3 in the green anole reveals that microchromosomes have significantly higher values than macrochromosomes, and this is similar to the chicken pattern [Figuet et al, 2014]. It is reported that the local GC content of snakes shows the presence of isochore structures as observed in turtles and crocodiles [Yin et al, 2016]. The GC content can be increased by the process of GC-biased gene conversion [Duret and Galtier, 2009].…”
Section: Discussionmentioning
confidence: 58%
“…Analysis of GC3 in the green anole reveals that microchromosomes have significantly higher values than macrochromosomes, and this is similar to the chicken pattern [Figuet et al, 2014]. It is reported that the local GC content of snakes shows the presence of isochore structures as observed in turtles and crocodiles [Yin et al, 2016]. The GC content can be increased by the process of GC-biased gene conversion [Duret and Galtier, 2009].…”
Section: Discussionmentioning
confidence: 58%
“…First, there is extensive variation in their TE content, ranging from 31.82% readily identifiable TEs (in the Burmese Python) to 49.6% (in the legless anguid lizard). While there have been extensive gene family expansions and contractions in squamate lineages, no clear correlations have been found linking these to TE content fluctuations [Yin et al, 2016]. The diversity in genomic TE landscapes is best exemplified in snakes.…”
Section: The Diversity Of Reptilian Mobilomementioning
confidence: 99%
“…Older (divergent) copies of L1 and L2 occur in both basal and advanced groups of snakes, suggesting these elements were more active in ancestral snakes [Yin et al, 2016]. While recent expansions include the snake1 CR1 LINEs that have primarily expanded in colubroid snakes [Castoe et al, 2013], expansion of DNA transposons ( hAT-Charlie, Tc1/Mariner ) and LTR ( Gypsy ) sequences have occurred in the viper genomes and L2 and CR1 in boas and pythons [Yin et al, 2016]. Such recent TE expansions of elements suggest that the repetitive fraction of squamate genomes remains highly dynamic.…”
Section: The Diversity Of Reptilian Mobilomementioning
confidence: 99%
See 1 more Smart Citation
“…Cytogenetic and individual gene studies suggest an astounding diversity of both ZW and XY sex chromosome systems in other vertebrate lineages ). However, while various studies have shed light on sex chromosome evolution in reptiles and fishes (e.g., Chen et al 2014;White et al 2015;Rovatsos et al 2016;Yin et al 2016;Rupp et al 2017), integrated genome-scale investigations of the origins and functional adaptations of vertebrate sex chromosomes outside of mammals and birds remain scarce.…”
mentioning
confidence: 99%